PEMIKIRAN ETIKA IBNU MISKAWAIH - Awal; Santalia, Indo (Living Islam: Journal of Islamic Discourses, 2023)
Abstract Ibn Miskawaih is known as the father of Islamic ethics. He has been able to formulate the basics of ethics in his book Tahdzib al Akhlaq wa Thathir al A'raq (Education Budi and Cleansing Morals). The source of Ibn Miskawaih's ethical philosophy comes from Greek philosophy, Persian civilization, Islamic teachings and personal experience. In His thoughts on ethics, he started by exploring the human soul. He views that psychology has its own virtues compared to other other psychology. Ibn Miskawaih's ethical teachings stem from the bitch theory middle. The point is to say that moral virtue is generally defined as as a middle position, extreme advantages and extreme disadvantages of each human soul. Thus, according to Ibn Miskawaih that morality is a a state of mind that invites someone to act without thinking and calculated beforehand. So that morality can be made into human nature by doing continuous exercises until it becomes a good self give birth to good morals. Keywords: Ibn Miskawaih, Ethics, morality   Abstrak Ibnu Miskawaih dikenal sebagai bapak etika Islam. Dia mampu merumuskan dasar-dasar etika dalam bukunya Tahdzib al Akhlaq wa Thathir al A'raq (Pendidikan Budi dan pembersihan budi pekerti) . Sumber filsafat etika Ibnu Miskawaih berasal dari Filsafat Yunani, peradaban Persia, ajaran Islam dan pengalaman pribadi. Di Pemikirannya tentang etika, ia mulai dengan menjelajahi jiwa manusia. Dia bahwa psikologi memiliki keutamaan tersendiri dibandingkan dengan yang lain psikologi lainnya. Ajaran etika Ibn Miskawaih berasal dari teori anjing betina lingkungan. Ini untuk mengatakan bahwa kebajikan moral secara umum didefinisikan sebagai sebagai posisi tengah, keuntungan ekstrim dan kerugian ekstrim masing-masing jiwa manusia. Jadi, menurut Ibnu Miskawaih, akhlak adalah keadaan pikiran yang mengajak seseorang untuk bertindak tanpa berpikir dan dihitung sebelumnya. Sehingga moralitas dapat menjelma menjadi fitrah manusia dengan melakukan latihan terus menerus sampai ia menjadi diri yang baik melahirkan akhlak yang baik. Kata Kunci: Ibnu Miskawaih, Etika, akhlak.